\( \overrightarrow{F H} \) bisects \( \angle E F G \). Find the indicated angle measures. \( m \angle E F H=63^{\circ} \). Find \( m \angle G F H \) and \( m \angle E F G \). \( m \angle G F H=\square^{\circ} \) \( m \angle E F G=\square^{\circ} \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Beyond the Answer
Since \( \overrightarrow{F H} \) bisects \( \angle E F G \), this means that the measures of the angles on either side of the bisector are equal. Given that \( m \angle E F H = 63^\circ \), we can conclude that: 1. \( m \angle G F H \) is also \( 63^\circ \) because both angles are equal due to the bisector's property. Now to find \( m \angle E F G \), we simply add the two equal angles together: \[ m \angle E F G = m \angle E F H + m \angle G F H = 63^\circ + 63^\circ = 126^\circ \] So, we have: \( m \angle G F H = 63^\circ \) \( m \angle E F G = 126^\circ \)